1997
DOI: 10.1091/mbc.8.12.2421
|View full text |Cite
|
Sign up to set email alerts
|

SET1, A Yeast Member of theTrithoraxFamily, Functions in Transcriptional Silencing and Diverse Cellular Processes

Abstract: The trithorax gene family contains members implicated in the control of transcription, development, chromosome structure, and human leukemia. A feature shared by some family members, and by other proteins that function in chromatin-mediated transcriptional regulation, is the presence of a 130- to 140-amino acid motif dubbed the SET or Tromo domain. Here we present analysis of SET1, a yeast member of the trithorax gene family that was identified by sequence inspection to encode a 1080-amino acid protein with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
221
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(236 citation statements)
references
References 65 publications
14
221
0
Order By: Relevance
“…The C-terminal region of ALL-1 and TRX includes the SET domain, which is highly conserved between the two proteins and is also present within the trx-G/Pc-G proteins ASH1 (Tripoulas et al, 1996) and E(Z) (Jones and Gelbart, 1993), in the functionally related Drosophila protein SU(VAR) 3 ± 9 (Tschiersch et al, 1994), in the ALL-1 related protein ALR (Prasad et al, 1997), and in a series of other proteins from yeast, fungi, C. elegans, plants and humans (Jenuwein et al, 1998;Nislow et al, 1997;Prasad et al, 1997). A TRX C-terminal segment containing amino acid residues 3375 ± 3759, which span the SET motif and some upstream sequences, was inserted into the pGBT9 vector and used in a two hybrid assay to screen a Drosophila third instar larvae cDNA library in pACT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal region of ALL-1 and TRX includes the SET domain, which is highly conserved between the two proteins and is also present within the trx-G/Pc-G proteins ASH1 (Tripoulas et al, 1996) and E(Z) (Jones and Gelbart, 1993), in the functionally related Drosophila protein SU(VAR) 3 ± 9 (Tschiersch et al, 1994), in the ALL-1 related protein ALR (Prasad et al, 1997), and in a series of other proteins from yeast, fungi, C. elegans, plants and humans (Jenuwein et al, 1998;Nislow et al, 1997;Prasad et al, 1997). A TRX C-terminal segment containing amino acid residues 3375 ± 3759, which span the SET motif and some upstream sequences, was inserted into the pGBT9 vector and used in a two hybrid assay to screen a Drosophila third instar larvae cDNA library in pACT.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, studies in yeast demonstrated that the S. cerevisiae SET 1 protein interacts through the SET motif with the checkpoint MEC3 protein involved in DNA repair and telomere function (Corda et al, 1999). Previously, the SET domain within yeast SET 1 was shown to play a direct role in telomeric silencing (Nislow et al, 1997), and the SET protein CLR4 of S. pombe was shown to be a modi®er of centromeric position e ects (silencing) (Ekwall et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This modification fully activates transcription of many genes, in part by facilitating the recruitment of the chromatinremodeling ATPase Isw1p to chromatin (15,16). In addition, several groups have reported a role for Set1p in silencing at the rDNA tandem repeats (14), telomeres (17,18), and the silent copy of the mating type HML (17). Although the role of Set1p in silencing at the rDNA seems to be independent of Sir2p (19), the amount of Sir2p associated to telomeres is synergistically reduced by mutations on Dot1p (lysine 79 H3 methyltransferase) and Set1p (lysine 4 H3 methyltransferase) (20).…”
mentioning
confidence: 99%
“…The functions of such domains have been implicated in the epigenetic control of developmental gene expression in Drosophila (38), proper sister chromatid segregation during meiosis (11), and telomeric and centromeric silencing in yeast (22,35). The molecular mechanisms that regulate these and other properties of higher-order chromatin are essentially unknown.…”
mentioning
confidence: 99%
“…These and other SET domain proteins have been shown to either physically or indirectly associate with chromatin (1,7,40). In yeast, mutations in the SET domains of CLR4 and SET1 disrupt centromeric silencing in Schizosaccharomyces pombe and telomeric silencing in Saccharomyces cerevisiae, respectively (22,35). Although found in over 30 proteins from human, Drosophila, Caenorhabditis elegans and yeast, the molecular functions for SET domains are not known.…”
mentioning
confidence: 99%